Intertextuality and Transtextuality: Theoretical Connections and Literary Illustrations (Texas Journal of Philology, Culture and History, 2025)
Intertextuality and transtextuality are pivotal concepts in contemporary literary theory for understanding how texts relate to one another. This article provides a concise overview of Julia Kristeva’s broad vision of intertextuality and Gerard Genette’s systematic taxonomy of transtextual relations. Kristeva’s notion of the text as a “mosaic of quotations” highlights the inherently dialogic nature of literature. Genette refines this view by distinguishing five types of transtextuality (intertextuality, paratextuality, metatextuality, hypertextuality, architextuality), offering precise tools for textual analysis. The article also examines how archetypes, motifs, and chronotopes serve as integrative analytical dimensions, revealing deep structural and symbolic linkages across works. Selected examples – from Homer’s Odyssey to Joyce’s Ulysses, from Pushkin to Bulgakov – illustrate how these frameworks illuminate literary interpretation. Together, they enable a richer comparative analysis by capturing both explicit references and the shared narrative patterns that bind literary texts.